2008
DOI: 10.1007/s11999-008-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

Shaped, Stratified, Scaffold-free Grafts for Articular Cartilage Defects

Abstract: One goal of treatment for large articular cartilage defects is to restore the anatomic contour of the joint with tissue having a structure similar to native cartilage. Shaped and stratified cartilaginous tissue may be fabricated into a suitable graft to achieve such restoration. We asked if scaffold-free cartilaginous constructs, anatomically shaped and targeting spherically-shaped hips, can be created using a molding technique and if biomimetic stratification of the shaped constructs can be achieved with appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…In addition to aiding implant design it has been suggested that characterising the acetabulum cartilage morphology could aid cartilage regeneration techniques (42). Current methods are limited by availability of donor tissue sources, donor site morbidity and prolonged rehabilitation times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to aiding implant design it has been suggested that characterising the acetabulum cartilage morphology could aid cartilage regeneration techniques (42). Current methods are limited by availability of donor tissue sources, donor site morbidity and prolonged rehabilitation times.…”
Section: Discussionmentioning
confidence: 99%
“…Current methods are limited by availability of donor tissue sources, donor site morbidity and prolonged rehabilitation times. Therefore second-generation tissue-engineered cartilaginous constructs which match the complex surface geometries of larger articular cartilage defects have been suggested to improve healing (42). Recently the hip has been suggested as a potential site for biologic resurfacing using shaped cartilaginous constructs in which a concave impression would be used to reconstruct the degenerated acetabulum (43).…”
Section: Discussionmentioning
confidence: 99%
“…There have been recent efforts to shape cartilaginous constructs using molding techniques. [40][41][42] Using molds with anatomical contours, the compaction method has the potential to mechanically impose a shape to the constructs or further maintain and improve the shaping fidelity of already-shaped constructs, which may facilitate fabrication of grafts for large cartilage defects with complex surface contours.…”
Section: Han Et Almentioning
confidence: 99%
“…This allowed efficient usage of the available animal tissue. Groups included [1] fresh controls (n ¼ 18) or joints incubated for [2] 12 days (n ¼ 6) or [3] 28 days (n ¼ 5) at 378C without CX, for [4] 28 days (n ¼ 4) at 48C without CX, for 7 days at 48C and then 7 days at 378C (4=37) [5] without CX (n ¼ 3) or [6] with CX (n ¼ 3), or for [7] 14 days at 378C with CX (n ¼ 3) (Fig. 1A).…”
Section: Experimental Designmentioning
confidence: 99%
“…1,2 The shortage of available donor tissue 3 has stimulated tissue engineering efforts to generate large, appropriately shaped, joint-scale osteochondral fragments. [4][5][6][7][8] Allografts are currently stored at the joint scale, and the properties of cartilage in such stored allografts provide the standard for large tissue-engineered constructs.…”
Section: Introductionmentioning
confidence: 99%